Antibacterial ceramic and preparation method thereof

By using specific combinations of ceramic raw materials and antibacterial agents and using a three-stage step-by-step temperature-controlled firing process, the problem of poor bacterial control effect of existing antibacterial ceramics during high-temperature firing is solved, and efficient and long-lasting antibacterials are achieved. Multiple performance improvements in effect and ceramic products.

CN119390426AInactive Publication Date: 2025-02-07DEHUAQIAO CRAFTSMAN CERAMIC TECH CO LTD
View PDF 0 Cites 6 Cited by

Patent Information

Application Number
CN202411544925.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing antibacterial ceramics have poor bacteria control effects during high-temperature firing, and titanium-based antibacterial ceramics require photocatalysis to sterilize, resulting in poor antibacterial properties and difficult to meet the needs of use.

Method used

Using combined raw materials including kaolin, diatomaceous earth, montmorillonite, soapite, bamboo charcoal powder, nanocopper oxide, nanosilver and zeolite, apatite, and zirconium phosphate, it is formed by ball milling and filtration, sintering and glazing, using three The step-step temperature-raising control firing process is used in combination with the use of antibacterial agents such as nano zinc oxide, nano titanium dioxide and zinc silicate.

Benefits of technology

It improves the antibacterial durability and effect of antibacterial ceramics, enhances the tightness, crack resistance and deformation resistance of the ceramics, and improves the aesthetics and durability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005113535910000131
    Figure BDA0005113535910000131
  • Figure BDA0005113535910000141
    Figure BDA0005113535910000141
  • Figure BDA0005113535910000151
    Figure BDA0005113535910000151
Patent Text Reader

Abstract

The invention provides antibacterial ceramic and a preparation method thereof. The antibacterial ceramic comprises a blank body and a glaze layer, the blank body is prepared from the following raw materials: kaolin, diatomite, montmorillonite, soapstone, bamboo charcoal powder, a first antibacterial agent, a fluxing agent, a pore forming agent, an adhesive and a reinforcing agent; the glaze layer comprises the following raw materials: kaolin, diatomite, dolomite, tourmaline, sodium oxide, a second antibacterial agent, a binder, a stabilizer and a dispersant. The method comprises the following steps: firing a molded green body by adopting stepped segmented heating, and carrying out glaze firing by adopting stepped segmented heating after glazing, thereby obtaining the antibacterial ceramic. According to the antibacterial ceramic disclosed by the invention, the antibacterial agent is added into the green body and the glaze layer, so that the influence on the antibacterial property of the green body in the firing process of the green body is avoided, the antibacterial durability is further improved, the antibacterial effect is enhanced, and the antibacterial rate on pathogenic bacteria such as escherichia coli and staphylococcus aureus reaches 99.99%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, in particular to an antibacterial ceramic and a preparation method thereof. Background Art

[0002] Among antibacterial ceramics, silver-based antibacterial ceramics and titanium-based antibacterial ceramics are the most common. Silver-based antibacterial effect is very good, but when silver ions are applied to ceramics, they will volatilize during high-temperature firing, resulting in poor bacteria control effect; titanium-based antibacterial ceramics have poor bacteria control effect when fired at high temperatures, and require photocatalysis to kill bacteria, resulting in poor antibacterial properties, which is difficult to meet usage requirements. Summary of the invention

[0003] In order to solve the above-mentioned deficiencies of the prior art, the object of the present invention is to provide an antibacterial ceramic and a preparation method thereof to overcome the defects in the prior art.

[0004] In order to achieve the above-mentioned purpose, the present invention provides an antibacterial ceramic, which includes a body and a glaze layer; the body includes the following raw materials in parts by weight: 30-40 parts of kaolin, 10-15 parts of diatomaceous earth, 5-10 parts of montmorillonite, 10-15 parts of saponite, 5-10 parts of bamboo charcoal powder, 5-10 parts of a first antibacterial agent, 1-5 parts of a flux, 5-8 parts of a first binder, and 1-3 parts of a reinforcing agent; the glaze layer includes the following raw materials in parts by weight: 15-25 parts of kaolin, 10-15 parts of diatomaceous earth, 10-15 parts of dolomite, 3-5 parts of tourmaline, 1-3 parts of sodium oxide, 5-10 parts of a second antibacterial agent, 1-3 parts of a second binder, 1-3 parts of a stabilizer, 1-3 parts of a dispersant, and 0.5-1 parts of a wear-resistant additive.

[0005] As a further description of the antibacterial ceramics described in the present invention, preferably, the antibacterial ceramics include a body and a glaze layer; the body includes the following raw materials in parts by weight: 35 parts of kaolin, 12 parts of diatomaceous earth, 8 parts of montmorillonite, 12 parts of saponite, 7 parts of bamboo charcoal powder, 8 parts of a first antibacterial agent, 3 parts of a flux, 6 parts of a first binder, and 2 parts of a reinforcing agent; the glaze layer includes the following raw materials in parts by weight: 20 parts of kaolin, 12 parts of diatomaceous earth, 11 parts of dolomite, 4 parts of tourmaline, 2 parts of sodium oxide, 8 parts of a second antibacterial agent, 2 parts of a second binder, 2 parts of a stabilizer, 2 parts of a dispersant, and 0.8 parts of a wear-resistant additive.

[0006] As a further description of the antibacterial ceramic of the present invention, preferably, in the embryo, the first antibacterial agent includes nano copper oxide, nano silver and at least one selected from zeolite, apatite and zirconium phosphate; the flux includes potassium oxide powder and sodium silicate; the first binder includes bentonite, sodium carboxymethyl cellulose and sodium silicate; the reinforcing agent includes inorganic fiber and inorganic powder, the inorganic fiber is selected from at least one of mullite fiber, aluminum silicate fiber and basalt fiber, and the inorganic powder is selected from at least one of aluminum oxide powder, silicon carbide powder and zirconium oxide powder; the particle diameter of the first antibacterial agent is 50-80nm; the average particle size of the flux, the first binder and the reinforcing agent is 10-15μm. More preferably, the flux is formed by mixing potassium oxide powder and sodium silicate in a mass ratio of 2:1; the first binder is formed by mixing bentonite, sodium carboxymethyl cellulose and sodium silicate in a mass ratio of 1:1:2; the reinforcing agent is formed by mixing inorganic fiber and inorganic powder in a mass ratio of 1:1.

[0007] As a further illustration of the antibacterial ceramic of the present invention, preferably, in the embryo, the particle sizes of the kaolin, diatomaceous earth, montmorillonite, saponite and bamboo charcoal powder are all 300-350 meshes.

[0008] As a further explanation of the antibacterial ceramic of the present invention, preferably, in the glaze layer, the second antibacterial agent includes nano zinc oxide, nano titanium dioxide and at least one selected from zinc silicate, zinc phosphate and zinc nitrate; the second binder includes polyvinyl alcohol and bentonite; the stabilizer includes zirconium silicate and magnesium oxide; the dispersant includes hydroxymethyl cellulose, sodium silicate, sodium hexametaphosphate and polyacrylamide; the wear-resistant additive includes wollastonite and calcium phosphate; the particle diameter of the second antibacterial agent is 50-80nm; the average particle size of the second binder, stabilizer, dispersant and wear-resistant additive is 10-15μm. More preferably, the second binder is a mixture of polyvinyl alcohol and bentonite in a mass ratio of 1:0.5; the stabilizer is a mixture of zirconium silicate and magnesium oxide in a mass ratio of 1:1; the dispersant is a mixture of hydroxymethyl cellulose, sodium silicate, sodium humate and polyacrylamide in a mass ratio of 1:1:1:2; the wear-resistant additive is a mixture of wollastonite and calcium phosphate in a mass ratio of 1:0.8.

[0009] As a further illustration of the antibacterial ceramic of the present invention, preferably, in the glaze layer, the particle sizes of the kaolin, diatomaceous earth, dolomite and tourmaline are all 300-350 meshes.

[0010] In order to achieve another object of the present invention, the present invention also provides a method for preparing an antibacterial ceramic, the preparation method comprising the following steps:

[0011] Step 1): according to the raw materials of the green body, kaolin, diatomaceous earth, montmorillonite, saponite and bamboo charcoal powder are weighed and then mixed, and water is added to the mixture in a ball mill for ball milling and impurity removal to obtain a slurry;

[0012] Step 2): Add the first antibacterial agent, flux, first binder and reinforcing agent to the slurry obtained in step 1) and mix thoroughly, filter press and shape into a ceramic body, and then sinter after drying. At room temperature, heat up to 200-300° C. at a uniform rate, and fire for 3-3.5 hours. Then heat up to 850-950° C. at a uniform rate, and fire for 5-6 hours. Then heat up to 1150-1250° C. at a uniform rate, and fire for 2-2.5 hours. Finally, cool naturally to room temperature and fire into a shape.

[0013] Step 3): according to the raw materials of the glaze layer, kaolin, diatomaceous earth, dolomite and tourmaline are weighed and mixed, water is added in a ball mill, the mixture is ball-milled and impurities are removed, and then sodium oxide, a second antibacterial agent, a second binder, a stabilizer, a dispersant and a wear-resistant additive are added, and ultrasonic stirring is performed at a speed of 400-500 r / min for 30-40 minutes to obtain a glaze slurry;

[0014] Step 4): The ceramic glaze slurry obtained in step 3) is evenly glazed onto the fired ceramic body obtained in step 2) to form a glaze layer. After the glaze layer on the ceramic body is dried, it is glazed and fired. At room temperature, the temperature is increased to 450°C-550°C in 2-3h, then increased to 950-1050°C in 1-2h, kept warm for 1.5-2min, then increased to 1250-1350°C in 0.5-1h, kept warm for 30min, and finally naturally cooled to room temperature to obtain the antibacterial ceramic.

[0015] As a further illustration of the preparation method of the present invention, preferably, in step 2), the moisture content of the ceramic body is 20-25%; and in step 3), the moisture content of the ceramic glaze slurry is 45-55%.

[0016] As a further illustration of the preparation method of the present invention, preferably, the thickness of the glaze layer in step 4) is 0.6-0.8 mm.

[0017] The beneficial effects of the present invention are as follows:

[0018] The green body of the present invention uses kaolin, diatomaceous earth, montmorillonite, soapstone and bamboo charcoal powder as main raw materials, and is added with a first antibacterial agent, which is a combination antibacterial agent of nano copper oxide, nano silver, and at least one of zeolite, apatite and zirconium phosphate. The porous structures of zeolite and apatite and the mesoporous structure of zirconium phosphate can be used as good carriers of nano silver and nano copper oxide, and the nano silver and nano copper oxide particles are fixed by physical adsorption or chemical bonding. Zeolite, apatite and zirconium phosphate have good thermal stability, maintain structural integrity at high temperature to protect nano silver and nano copper oxide, reduce the influence of nano silver and nano copper oxide on the antibacterial property of the green body during the firing process, thereby improving the stability and antibacterial durability of nano silver and nano copper oxide, and enhancing the antibacterial effect.

[0019] In the green body of the present invention, by adding a flux mixed by potassium oxide powder and sodium silicate, the firing temperature of the green body can be reduced, the raw material melting can be promoted, and the density of the green body can be improved; by adding a first binder mixed by bentonite, sodium carboxymethyl cellulose and sodium silicate, the bonding compatibility between kaolin, diatomite, montmorillonite, soapstone and bamboo charcoal powder is increased, the strength of the green body is improved, and during the green body firing process, it is helpful to uniformly discharge the internal moisture of the green body, adjust the drying shrinkage and firing shrinkage of the green body, and improve the compactness and crack resistance of the green body; by adding a reinforcing agent mixed by inorganic fiber (at least one of mullite fiber, aluminum silicate fiber and basalt fiber) and inorganic powder (at least one of aluminum oxide powder, silicon carbide powder and zirconium oxide powder), the inorganic fiber improves the crack resistance of the green body during the firing process, increases the toughness of the green body, and the inorganic powder helps to improve the density of ceramics during the sintering process. Therefore, the ceramic green body of the present invention is not only high in strength, but also has good compactness, crack resistance and deformation resistance.

[0020] The glaze layer of the present invention uses kaolin, diatomite, dolomite, tourmaline and sodium oxide as basic raw materials, dolomite has a glaze silky effect, tourmaline has a function of improving the glaze hardness and the infrared radiation rate of the glaze, and sodium oxide has a fluxing effect, shortening the glaze firing time; by adding a second antibacterial agent, a combination antibacterial agent of nano zinc oxide, nano titanium dioxide, and at least one of zinc silicate, zinc phosphate and zinc nitrate is prepared. The added zinc silicate, zinc phosphate and zinc nitrate can be wrapped on the surface of nano zinc oxide and nano titanium dioxide, improve the fluidity of the glaze, and the nano zinc oxide and nano titanium dioxide can be evenly dispersed in the glaze, and during the glaze firing process, the high temperature is avoided from destroying the antibacterial properties of the nano zinc oxide and nano titanium dioxide, and the photocatalytic effect of the nano zinc oxide and nano titanium dioxide is increased, thereby improving the antibacterial properties of the nano zinc oxide and nano titanium dioxide, and increasing the antibacterial durability.

[0021] The glaze layer of the present invention can improve the adhesion and hardness of the glaze, and enhance the smoothness, wear resistance and crack resistance of the glaze surface by adding a second binder mixed with polyvinyl alcohol and bentonite; by adding a stabilizer mixed with zirconium silicate and magnesium oxide, magnesium oxide can enhance the thermal stability of the glaze, and synergistically reduce the cracking and deformation of the glaze layer caused by temperature changes, thereby improving the crack resistance, deformation resistance and wear resistance of the ceramic product; by adding a dispersant mixed with hydroxymethyl cellulose, sodium silicate, sodium hexametaphosphate and polyacrylamide, hydroxymethyl cellulose can It can prevent problems such as cracking and deformation caused by water loss during the molding process. Sodium hexametaphosphate can improve the adhesion and hardness of the glaze, and synergistically improve the gloss and wear resistance of the glaze with sodium silicate. Polyacrylamide can reduce cracks and defects during the sintering process of the product, thereby increasing the overall crack resistance and deformation resistance of the ceramic. By adding a wear-resistant additive mixed with wollastonite and calcium phosphate, the hardness and wear resistance of the glaze can be improved, and calcium phosphate increases the hardness and wear resistance of the glaze, and reduces the defects of bubbles, bursts and cracks on the glaze, thereby improving the quality of the glaze. Therefore, the ceramic glaze layer of the present invention also has good density, crack resistance and deformation resistance.

[0022] The antibacterial ceramic of the present invention has a glaze layer with good wear resistance, uniformity and glossiness, thereby enhancing the light transmittance of the glaze surface and improving the aesthetics and durability of the ceramic product.

[0023] The preparation method of the present invention can obtain antibacterial ceramics with high strength, high density, crack resistance and deformation resistance by controlling the temperature and time of the ceramic body biscuit firing in three stages, and controlling the temperature and time of the glaze firing in three stages after the ceramic body is glazed. The antibacterial ceramic has antibacterial agents in both the body and the glaze layer to increase the antibacterial durability and antibacterial effect. DETAILED DESCRIPTION

[0024] In order to further understand the structure, features and other purposes of the present invention, the following detailed description is given in conjunction with the attached preferred embodiments. This embodiment is only used to illustrate the technical solution of the present invention and is not intended to limit the present invention.

[0025] Example 1: A method for preparing antibacterial ceramics

[0026] Preparation of ceramic green body: According to the weighing of green body raw materials, first weigh 30 parts of kaolin, 10 parts of diatomite, 5 parts of montmorillonite, 10 parts of soapstone and 5 parts of bamboo charcoal powder, all of which have a particle size of preferably 300 mesh, and then mix them, add water in a ball mill, mix and ball mill, remove impurities, and obtain mud. Then add 5 parts of the first antibacterial agent (including nano copper oxide, nano silver and zirconium phosphate in a mass ratio of 1:1:0.5, and the particle diameter is preferably 50nm), 1 part of flux (including potassium oxide powder and sodium silicate in a mass ratio of 2:1), 5 parts of the first binder (including bentonite, sodium carboxymethyl cellulose and sodium silicate in a mass ratio of 1:1:2), 1 part of reinforcing agent (including mullite fiber and alumina powder in a mass ratio of 1:1) to the obtained mud, mix them thoroughly, filter press, and shape them into a ceramic green body with a moisture content of 20%, and sinter them after drying. At room temperature, the temperature is uniformly raised to 200°C and fired for 3 hours, then uniformly raised to 850°C and fired for 5 hours, then uniformly raised to 1150°C and fired for 2 hours, and finally naturally cooled to room temperature and fired to form.

[0027] Preparation of ceramic glaze: According to the weight of the raw materials for the glaze layer, 15 parts of kaolin, 10 parts of diatomite, 10 parts of dolomite, and 3 parts of tourmaline, all of which have a particle size of preferably 300 mesh, are weighed and mixed, and water is added to the ball mill for mixing and ball milling to remove impurities. Then, 1 part of sodium oxide, 5 parts of the second antibacterial agent (including nano zinc oxide, nano titanium dioxide and zinc silicate in a mass ratio of 1:1:0.5), 1 part of the second binder (including polyvinyl alcohol and bentonite in a mass ratio of 1:0.5), 1 part of the stabilizer (including zirconium silicate and magnesium oxide in a mass ratio of 1:1), 1 part of the dispersant (including hydroxymethyl cellulose, sodium silicate, sodium hexametaphosphate and polyacrylamide in a mass ratio of 1:1:1:2), and 0.5 parts of the wear-resistant additive (including wollastonite and calcium phosphate in a mass ratio of 1:0.8) are added, and ultrasonic stirring is performed at a speed of 400r / min for 30 minutes to obtain a ceramic glaze slurry with a water content of 45%.

[0028] Preparation of antibacterial ceramic glaze firing: The obtained ceramic glaze slurry is evenly glazed onto the fired ceramic body to form a glaze layer. After the glaze layer on the ceramic body is dried, the glaze is fired. At room temperature, the temperature is raised to 450°C in 2 hours, then raised to 950°C in 1 hour, kept warm for 1.5 minutes, and then raised to 1250°C in 0.5 hours, kept warm for 30 minutes, to obtain an antibacterial ceramic with a glaze layer thickness of 0.6 mm.

[0029] Example 2: A method for preparing antibacterial ceramics

[0030] Preparation of ceramic green body: According to the weighing of green body raw materials, first weigh 35 parts of kaolin, 12 parts of diatomite, 8 parts of montmorillonite, 12 parts of soapstone, and 7 parts of bamboo charcoal powder, all of which have a particle size of preferably 320 mesh, and then mix them, add water in a ball mill, mix and ball mill, remove impurities, and obtain mud. Then add 8 parts of the first antibacterial agent (including nano copper oxide, nano silver and zirconium phosphate in a mass ratio of 1:1:0.5, and the particle diameter is preferably 65nm), 3 parts of flux (including potassium oxide powder and sodium silicate in a mass ratio of 2:1), 6 parts of the first binder (including bentonite, sodium carboxymethyl cellulose and sodium silicate in a mass ratio of 1:1:2), and 2 parts of reinforcing agent (including mullite fiber and alumina powder in a mass ratio of 1:1) to the obtained mud, mix them thoroughly, filter them, and shape them into a ceramic green body with a moisture content of 23%, and sinter them after drying. At room temperature, the temperature was uniformly raised to 250°C and fired for 3.2 hours, then uniformly raised to 900°C and fired for 5.5 hours, then uniformly raised to 1200°C and fired for 2.3 hours, and finally naturally cooled to room temperature and fired to form.

[0031] Preparation of ceramic glaze: According to the weight of the glaze layer raw materials, first weigh 20 parts of kaolin, 12 parts of diatomite, 11 parts of dolomite, and 4 parts of tourmaline, all of which have a particle size of preferably 320 mesh, and then mix them, add water in a ball mill, mix and ball mill, and remove impurities. Then add 2 parts of sodium oxide, 8 parts of the second antibacterial agent (including nano zinc oxide, nano titanium dioxide and zinc silicate in a mass ratio of 1:1:0.5), 2 parts of binder (including sodium silicate and sodium hexametaphosphate in a mass ratio of 1:1), 2 parts of stabilizer (including zirconium silicate and magnesium oxide in a mass ratio of 1:1), 2 parts of dispersant (including hydroxymethyl cellulose, sodium silicate, sodium humate and polyacrylamide in a mass ratio of 1:1:1:2), and ultrasonically stir at a speed of 45r / min for 35 minutes to obtain a ceramic glaze slurry with a water content of 48%.

[0032] Preparation of antibacterial ceramic glaze firing: The obtained ceramic glaze slurry is evenly glazed onto the fired ceramic body to form a glaze layer. After the glaze layer on the ceramic body is dried, the glaze is fired. At room temperature, the temperature is raised to 500°C in 2.5 hours, then raised to 1000°C in 1.5 hours, kept warm for 1.8 minutes, and then raised to 1300°C in 0.7 hours, kept warm for 30 minutes, to obtain an antibacterial ceramic with a glaze layer thickness of 0.7 mm.

[0033] Example 3: A method for preparing antibacterial ceramics

[0034] Preparation of ceramic green body: According to the weighing of green body raw materials, first weigh and mix 40 parts of kaolin, 15 parts of diatomite, 10 parts of montmorillonite, 15 parts of soapstone, and 10 parts of bamboo charcoal powder, all of which have a particle size of preferably 350 mesh, add water and mix in a ball mill, remove impurities, and obtain mud. Then add 10 parts of the first antibacterial agent (including nano copper oxide, nano silver and zirconium phosphate in a mass ratio of 1:1:0.5, and the particle diameter is preferably 80nm), 5 parts of flux (including potassium oxide powder and sodium silicate in a mass ratio of 2:1), 8 parts of the first binder (including bentonite, sodium carboxymethyl cellulose and sodium silicate in a mass ratio of 1:1:2), and 3 parts of reinforcing agent (including mullite fiber and alumina powder in a mass ratio of 1:1) to the obtained mud, mix thoroughly, filter press, and shape into a ceramic green body with a moisture content of 25%, and sinter after drying. At room temperature, the temperature is uniformly raised to 300°C and fired for 3.5 hours, then uniformly raised to 950°C and fired for 6 hours, then uniformly raised to 1250°C and fired for 2.5 hours, and finally naturally cooled to room temperature and fired to form.

[0035] Preparation of ceramic glaze: According to the weight of the glaze layer raw materials, first weigh 25 parts of kaolin, 15 parts of diatomite, 15 parts of dolomite, and 5 parts of tourmaline, all of which have a particle size of preferably 350 mesh, and then mix them, add water in a ball mill, mix and ball mill, and remove impurities. Then add 3 parts of sodium oxide, 10 parts of the second antibacterial agent (including nano zinc oxide, nano titanium dioxide and zinc silicate in a mass ratio of 1:1:0.5), 3 parts of the second binder (including sodium silicate and sodium hexametaphosphate in a mass ratio of 1:1), 3 parts of stabilizer (including zirconium silicate and magnesium oxide in a mass ratio of 1:1), 3 parts of dispersant (including hydroxymethyl cellulose, sodium silicate, sodium humate and polyacrylamide in a mass ratio of 1:1:1:2), 1 part of wear-resistant additive (including wollastonite and calcium phosphate in a mass ratio of 1:0.8), and ultrasonically stir at a speed of 500r / min for 40 minutes to obtain a ceramic glaze slurry with a water content of 55%.

[0036] Preparation of antibacterial ceramic glaze firing: The obtained ceramic glaze slurry is evenly glazed on the fired ceramic body to form a glaze layer. After the glaze layer on the ceramic body is dried, the glaze is fired. At room temperature, the temperature is raised to 550°C in 3 hours, then raised to 1050°C in 2 hours, kept warm for 2 minutes, and then raised to 1350°C in 1 hour, kept warm for 30 minutes, to obtain an antibacterial ceramic with a glaze layer thickness of 0.8 mm.

[0037] Embodiment 4:

[0038] This embodiment 4 refers to the method of embodiment 2, and the difference from embodiment 2 is that the first antibacterial agent in the step of preparing the ceramic body is nano copper oxide, nano silver and zeolite in a mass ratio of 1:1:0.5; the second antibacterial agent in the step of preparing the ceramic glaze is nano zinc oxide, nano titanium dioxide and zinc phosphate in a mass ratio of 1:1:0.5. See Table 1.

[0039] Embodiment 5:

[0040] This Example 5 refers to the method of Example 2, and the difference from Example 2 is that the first antibacterial agent in the step of preparing the ceramic body is nano copper oxide, nano silver and apatite in a mass ratio of 1:1:0.5; the second antibacterial agent in the step of preparing the ceramic glaze is nano zinc oxide, nano titanium dioxide and zinc nitrate in a mass ratio of 1:1:0.5. See Table 1.

[0041] Embodiment 6:

[0042] This Example 6 refers to the method of Example 2, and the difference from Example 2 is that the reinforcing agent in the step of preparing the ceramic body is aluminum silicate fiber and silicon carbide powder in a mass ratio of 1:1. See Table 1.

[0043] Embodiment 7:

[0044] This Example 7 refers to the method of Example 2, and the difference from Example 2 is that the reinforcing agent in the step of preparing the ceramic body is basalt fiber and zirconium oxide powder in a mass ratio of 1:1. See Table 1.

[0045] Embodiment 8:

[0046] This Example 8 refers to the method of Example 2, and the difference from Example 2 is that in the step of preparing the ceramic body, the reinforcing agent is mullite fiber, aluminum silicate fiber, aluminum oxide powder and silicon carbide powder in a mass ratio of 0.5:0.5:0.5:0.5. See Table 1.

[0047] Embodiment 9:

[0048] This Example 9 refers to the method of Example 2, and the difference from Example 2 is that the reinforcing agent in the step of preparing the ceramic body is aluminum silicate fiber, basalt fiber, aluminum oxide powder and zirconium oxide powder in a mass ratio of 0.5:0.5:0.5:0.5. See Table 1.

[0049] Comparative Example 1:

[0050] This comparative example 1 refers to the preparation method of the antibacterial ceramic of example 2, and the difference from example 2 is that when preparing the ceramic body, the first antibacterial agent is 8 parts of nano copper oxide and nano silver in a mass ratio of 1:1; when preparing the ceramic glaze, the second antibacterial agent is 8 parts of nano zinc oxide and nano titanium dioxide in a mass ratio of 1:1. See Table 1.

[0051] Comparative Example 2:

[0052] This comparative example 2 refers to the preparation method of the antibacterial ceramic of example 2, and the difference from example 2 is that when preparing the ceramic body, the flux is 3 parts of potassium oxide powder or 3 parts of sodium silicate. See Table 1.

[0053] Comparative Example 3:

[0054] This comparative example 3 refers to the preparation method of the antibacterial ceramic of example 2, and the difference from example 2 is that when preparing the ceramic body, the first binder is 6 parts of bentonite or 6 parts of sodium carboxymethyl cellulose or 6 parts of sodium silicate. See Table 1.

[0055] Comparative Example 4:

[0056] This comparative example 4 refers to the preparation method of the antibacterial ceramic of example 2, and the difference from example 2 is that when preparing the ceramic body, the reinforcing agent is 2 parts of mullite fiber or 2 parts of aluminum silicate fiber or basalt fiber. See Table 1.

[0057] Comparative Example 5:

[0058] This comparative example 5 refers to the preparation method of the antibacterial ceramic of example 2, and the difference from example 2 is that when preparing the ceramic body, the reinforcing agent is 2 parts of alumina powder or 2 parts of silicon carbide powder or 2 parts of zirconium oxide powder. See Table 1.

[0059] Comparative Example 6:

[0060] This comparative example 6 refers to the preparation method of the antibacterial ceramic of example 2, and the difference from example 2 is that when preparing the ceramic glaze layer, the second binder is 2 parts of polyvinyl alcohol or 2 parts of bentonite. See Table 1.

[0061] Comparative Example 7:

[0062] This comparative example 7 refers to the preparation method of the antibacterial ceramic of example 2, and the difference from example 2 is that when preparing the ceramic glaze layer, the stabilizer is 2 parts of zirconium silicate or 2 parts of magnesium oxide. See Table 1.

[0063] Comparative Example 8:

[0064] This comparative example 8 refers to the preparation method of the antibacterial ceramic of example 2, and the difference from example 2 is that when preparing the ceramic glaze layer, the dispersant is 2 parts of hydroxymethyl cellulose or 2 parts of sodium silicate or 2 parts of sodium humate or 2 parts of polyacrylamide. See Table 1.

[0065] Comparative Example 9:

[0066] This comparative example 9 refers to the preparation method of the antibacterial ceramic of example 2, and the difference from example 2 is that when preparing the ceramic glaze layer, the wear-resistant additive is 2 parts of wollastonite or 2 parts of calcium phosphate. See Table 1.

[0067] Comparative Example 10:

[0068] The preparation method of the antibacterial ceramic of this comparative example 10 refers to that of the example 2, and the difference from the example 2 is that when preparing the ceramic body, the temperature is directly raised to 1150-1250°C and fired for 10-12h.

[0069] The preparation method of the antibacterial ceramic of this comparative example 11 refers to that of example 2, and the difference from example 2 is that when preparing the antibacterial ceramic, the glaze firing temperature is directly raised to 1250-1350°C and fired for 5-8h.

[0070] Table 1

[0071]

[0072]

[0073]

[0074]

[0075]

[0076]

[0077]

[0078]

[0079] Example 10: Performance test experiment:

[0080] 1. Antibacterial test

[0081] Antibacterial ceramics were prepared by the methods of Examples 1-9 and Comparative Example 1. The test was carried out according to the Antibacterial Performance of Antibacterial Ceramic Products (JC / T897-2014), and each antibacterial ceramic sample was tested three times in parallel. The test results are shown in Table 2:

[0082] Table 2

[0083]

[0084] Combining the data of the antibacterial rates and antibacterial durability of Staphylococcus aureus and Escherichia coli in Examples 1-9 and Comparative Example 1 in Table 2, it can be seen that:

[0085] The antibacterial rates and antibacterial durability of the antibacterial ceramics obtained in Examples 1-9 of the present invention against Staphylococcus aureus and Escherichia coli are higher than those in Comparative Example 2.

[0086] In Examples 1-9 of the present invention, when preparing the ceramic body, the first antibacterial agent used is a combination antibacterial agent of nano-copper oxide, nano-silver, and at least one of zeolite, apatite, and zirconium phosphate; the porous structure of zeolite and apatite and the mesoporous structure of zirconium phosphate can serve as good carriers of nano-silver and nano-copper oxide, and fix the nano-silver and nano-copper oxide particles by physical adsorption or chemical bonding. Zeolite, apatite, and zirconium phosphate have good thermal stability, maintain structural integrity at high temperatures to protect nano-silver and nano-copper oxide, and reduce the influence of nano-silver and nano-copper oxide on its antibacterial properties during the firing process of the body, thereby improving the stability and antibacterial durability of nano-silver and nano-copper oxide, and enhancing the antibacterial effect.

[0087] In Examples 1-9 of the present invention, when preparing ceramic glazes, the second antibacterial agent is a combination antibacterial agent of nano zinc oxide, nano titanium dioxide, and at least one of zinc silicate, zinc phosphate, and zinc nitrate. The added zinc silicate, zinc phosphate, and zinc nitrate can be wrapped on the surface of nano zinc oxide and nano titanium dioxide, improve the fluidity of the glaze, and the nano zinc oxide and nano titanium dioxide can be evenly dispersed in the glaze, and during the glaze firing process, the high temperature is avoided from destroying the antibacterial properties of nano zinc oxide and nano titanium dioxide, and the photocatalytic effect of nano zinc oxide and nano titanium dioxide is increased, thereby improving the antibacterial properties of nano zinc oxide and nano titanium dioxide, and increasing the antibacterial persistence.

[0088] In comparative example 2, when preparing the ceramic body, the first antibacterial agent is nano copper oxide and nano silver; when preparing the ceramic glaze, the second antibacterial agent is nano zinc oxide and nano titanium dioxide. It can be seen that the present invention adds zeolite, apatite or zirconium phosphate and nano copper oxide and nano silver in the body, and adds zinc silicate, zinc phosphate or zinc nitrate and nano zinc oxide and nano titanium dioxide in the glaze, which has the effect of enhancing the antibacterial effect.

[0089] 2. Testing of deformation and cracking of fired ceramic body surface

[0090] The fired ceramic green bodies were prepared by the methods of Examples 1-9 and Comparative Examples 2-5, and the surface of the green bodies was observed for deformation and cracking. The results of each comparative example are the comprehensive results of multiple tests conducted under the conditions of temperature, time, etc. of Examples 1-9. The test results are shown in Table 3:

[0091] Table 3

[0092] Is the surface of the blank deformed? Is there any crack on the surface of the blank? Example 1 none none Example 2 none none Example 3 none none Example 4 none none Example 5 none none Example 6 none none Example 7 none none Example 8 none none Example 9 none none Comparative Example 2 Deformation Occasionally cracking Comparative Example 3 Occasionally deformed Slight cracking Comparative Example 4 Occasionally deformed Slight cracking Comparative Example 5 Occasionally deformed Slight cracking

[0093] Combining the data of Examples 1-9 and Comparative Examples 2-5 in Table 3 to observe whether the surface of the fired ceramic body is deformed and cracked, it can be seen that:

[0094] The surfaces of the ceramic bodies fired in Examples 1-9 of the present invention had no deformation or cracking; however, the surfaces of the ceramic bodies fired in Comparative Examples 2-5 were found to be deformed or cracked after multiple tests.

[0095] In Comparative Example 2, the flux is a single substance, and deformation and cracking occur on the surface of the fired green body. It can be seen that the flux compounded with potassium oxide powder and sodium silicate in the present invention helps to reduce the deformation and cracking of the green body to a certain extent.

[0096] In contrast to Example 3, the first binder used a single substance, and deformation and cracking occurred on the surface of the fired green body. It can be seen that the first binder compounded with bentonite, sodium carboxymethyl cellulose and sodium silicate in the present invention helps to reduce the deformation and cracking of the green body to a certain extent.

[0097] In contrast to the case where the reinforcing agent in Examples 4-5 is a single substance, deformation and cracking may occur on the surface of the fired green body. It can be seen that the reinforcing agent of the present invention, which is a composite of inorganic fiber and inorganic powder, helps to reduce the deformation and cracking of the green body to a certain extent.

[0098] 3. Test on deformation and cracking of ceramic glaze surface

[0099] The antibacterial ceramics made by glazing the ceramic bodies fired by the methods of Examples 1-9 and Comparative Examples 6-9 were observed to see whether the glaze surface was deformed and cracked. The results of each comparative example are the comprehensive results of multiple tests conducted under the conditions of temperature, time, etc. in reference to Examples 1-9. The test results are shown in Table 4:

[0100] Table 4

[0101] Is the glaze surface deformed? Is the glaze surface cracked? Example 1 none none Example 2 none none Example 3 none none Example 4 none none Example 5 none none Example 6 none none Example 7 none none Example 8 none none Example 9 none none Comparative Example 6 Deformation Slight cracking Comparative Example 7 Deformation Slight cracking Comparative Example 8 Deformation Slight cracking Comparative Example 9 Deformation Slight cracking

[0102] Combining the data of Examples 1-9 and Comparative Examples 6-9 in Table 4 to observe whether the surface of the fired ceramic glaze layer is deformed and cracked, it can be seen that:

[0103] The surfaces of the ceramic glaze layers fired in Examples 1-9 of the present invention had no deformation or cracking; however, the surfaces of the glaze layers of Comparative Examples 6-9 were subjected to multiple tests and deformation or cracking was found.

[0104] In Comparative Example 6, the second binder is a single substance, and the fired glaze layer surface will be deformed and cracked. It can be seen that the second binder compounded with polyvinyl alcohol and bentonite in the present invention helps to reduce the deformation and cracking of the glaze layer to a certain extent.

[0105] In Comparative Example 7, the stabilizer is a single substance, and the fired glaze layer surface will be deformed and cracked. It can be seen that the stabilizer of zirconium silicate and magnesium oxide added in the present invention helps to reduce the deformation and cracking of the glaze layer to a certain extent.

[0106] In contrast to Example 8, in which a single substance was used as the dispersant, deformation and cracking occurred on the surface of the fired glaze layer. It can be seen that the dispersant compounded with hydroxymethyl cellulose, sodium silicate, sodium hexametaphosphate and polyacrylamide in the present invention helps to reduce the deformation and cracking of the glaze layer to a certain extent.

[0107] In Comparative Example 9, the wear-resistant additive used a single substance, and the glaze layer surface was deformed and cracked. It can be seen that the wear-resistant additive compounded with wollastonite and calcium phosphate in the present invention helps to reduce the deformation and cracking of the glaze layer to a certain extent.

[0108] 4. Test on the effect of firing temperature on the surface of ceramic body and deformation and cracking of ceramic body

[0109] 4.1. Prepare fired ceramic green bodies by the methods of Examples 1-3 and Comparative Example 10, and observe whether the green body surface is deformed and cracked. The test results are shown in Table 5:

[0110] Table 5

[0111]

[0112]

[0113] Combining the data of Examples 1-3 and Comparative Example 10 in Table 5 to observe whether the surface of the fired ceramic body is deformed and cracked, it can be seen that:

[0114] The preparation methods of Examples 1-3 of the present invention control the temperature and time of the ceramic body bisque firing in three stages, and the fired body surface is free of deformation and cracking. However, the preparation method of Comparative Example 10 uses a direct heating method, and the fired body surface will be deformed and cracked.

[0115] 4.2. Antibacterial ceramics were prepared by the methods of Examples 1-3 and Comparative Example 11, and the surface of the glaze layer was observed to see whether it was deformed or cracked. The test results are shown in Table 6:

[0116] Table 6

[0117] Is the glaze surface deformed? Is the glaze surface cracked? Example 1 none none Example 2 none none Example 3 none none Comparative Example 11 Deformation There is cracking

[0118] Combining the data of Examples 1-3 and Comparative Example 11 in Table 6 to observe whether the surface of the fired ceramic glaze layer is deformed and cracked, it can be seen that:

[0119] The preparation methods of Examples 1-3 of the present invention control the temperature and time of glaze firing in three stages after glazing the ceramic body, and the fired glaze layer has no deformation or cracking on the surface. However, the preparation method of Comparative Example 11 uses a direct heating method, and the fired glaze layer has deformation and cracking on the surface.

[0120] 5. Density test of antibacterial ceramics

[0121] The fired ceramic bodies and the glaze layers of the antibacterial ceramics obtained after glazing were prepared by the methods of Examples 1-9 and Comparative Examples 2-9, and the densities of the bodies and the glaze layers were measured respectively. The test results are shown in Table 7:

[0122] Table 7

[0123] <![CDATA[Green body density (g / cm 2 )]]> <![CDATA[Glaze layer density (g / cm 2 )]]> Example 1 3.18 2.74 Example 2 3.24 2.81 Example 3 3.31 2.89 Example 4 3.23 2.81 Example 5 3.24 2.81 Example 6 3.22 2.81 Example 7 3.23 2.81 Example 8 3.24 2.81 Example 9 3.23 2.81 Comparative Example 2 2.92 - Comparative Example 3 2.91 - Comparative Example 4 2.87 - Comparative Example 5 2.85 - Comparative Example 6 - 2.56 Comparative Example 7 - 2.51 Comparative Example 8 - 2.48 Comparative Example 9 - 2.45

[0124] Combining the data of the green body density and glaze layer density of Examples 1-9 in Table 5, the green body density of Comparative Examples 2-5, and the glaze layer density of Comparative Examples 6-9, it can be seen that:

[0125] The green body density of the ceramic green bodies fired in Examples 1-9 of the present invention is significantly higher than that of Comparative Examples 1-5. Since the only difference between Comparative Examples 2-5 and Examples 1-9 of the present invention is that the corresponding flux, first binder, and reinforcing agent are respectively single substances, it can be seen that the compounded flux, first binder, and reinforcing agent added in the present invention help to increase the compactness of the green body to a certain extent.

[0126] The density of the glaze layer of the antibacterial ceramic obtained after glazing the ceramic bodies fired in Examples 1-9 of the present invention is significantly higher than that of the glaze layer of Comparative Examples 6-9. Since the difference between Comparative Examples 6-9 and Examples 1-9 of the present invention is only that the corresponding second binder, stabilizer, and dispersant are respectively single substances, it can be seen that the compounded second binder, stabilizer, and dispersant added in the present invention help to increase the density of the glaze layer to a certain extent.

[0127] It can be seen that the antibacterial ceramics obtained in Examples 1-9 of the present invention have higher density than the antibacterial ceramics obtained in Comparative Examples 2-9.

[0128] 6. Performance analysis of the raw materials of the antibacterial ceramic fired in the present invention

[0129] The green body of the present invention uses kaolin, diatomaceous earth, montmorillonite, soapstone and bamboo charcoal powder as main raw materials, and is added with a first antibacterial agent, which is a combination antibacterial agent of nano copper oxide, nano silver, and at least one of zeolite, apatite and zirconium phosphate. The porous structures of zeolite and apatite and the mesoporous structure of zirconium phosphate can be used as good carriers of nano silver and nano copper oxide, and the nano silver and nano copper oxide particles are fixed by physical adsorption or chemical bonding. Zeolite, apatite and zirconium phosphate have good thermal stability, maintain structural integrity at high temperature to protect nano silver and nano copper oxide, reduce the influence of nano silver and nano copper oxide on the antibacterial property of the green body during the firing process, thereby improving the stability and antibacterial durability of nano silver and nano copper oxide, and enhancing the antibacterial effect.

[0130] By adding a flux formed by mixing potassium oxide powder and sodium silicate into the green body of the present invention, the firing temperature of the green body can be reduced, the melting of raw materials can be promoted, and the density of the green body can be improved; potassium oxide can promote the formation of a glass phase at a high temperature and fill the gaps between crystal particles, and sodium silicate can refine the crystal particles, thereby improving the fineness and density of the green body and making the surface of the green body smoother and more beautiful.

[0131] The green body of the present invention increases the bonding compatibility among kaolin, diatomaceous earth, montmorillonite, soapstone and bamboo charcoal powder by adding the first binder which is a mixture of bentonite, sodium carboxymethyl cellulose and sodium silicate, improves the strength of the green body, and helps to evenly discharge the moisture inside the green body during the green body firing process, adjusts the drying shrinkage and firing shrinkage of the green body, and improves the compactness and crack resistance of the green body. Among them, bentonite has good adsorption. When sodium silicate and bentonite are mixed, the interlayer hydrated ions of the bentonite are replaced, so that the adsorption is enhanced, and the bonding compatibility among the raw materials of the green body is increased under the synergistic effect of sodium carboxymethyl cellulose.

[0132] In the green body of the present invention, a reinforcing agent mixed with inorganic fibers (at least one of mullite fibers, aluminum silicate fibers, and basalt fibers) and inorganic powders (at least one of aluminum oxide powders, silicon carbide powders, and zirconium oxide powders) is added, and the inorganic fibers improve the crack resistance of the green body during the firing process, increase the toughness of the green body, and thus improve the strength of the green body. In the sintering process, the inorganic powder helps to improve the density of the ceramic, reduce the sintering temperature and time, and optimize the sintering atmosphere to avoid excessive crystal growth, maintain a good microstructure, and thus improve the strength of the green body. Therefore, the ceramic green body of the present invention is not only high in strength, but also has good compactness, crack resistance, and deformation resistance.

[0133] 7. Performance analysis of the glaze material of the antibacterial ceramic of the present invention

[0134] The glaze layer of the present invention uses kaolin, diatomite, dolomite, tourmaline and sodium oxide as basic raw materials, dolomite has a glaze silky effect, tourmaline has a function of improving the glaze hardness and the infrared radiation rate of the glaze, and sodium oxide has a fluxing effect, shortening the glaze firing time; by adding a second antibacterial agent, a combination antibacterial agent of nano zinc oxide, nano titanium dioxide, and at least one of zinc silicate, zinc phosphate and zinc nitrate is prepared. The added zinc silicate, zinc phosphate and zinc nitrate can be wrapped on the surface of nano zinc oxide and nano titanium dioxide, improve the fluidity of the glaze, and the nano zinc oxide and nano titanium dioxide can be evenly dispersed in the glaze, and during the glaze firing process, the high temperature is avoided from destroying the antibacterial properties of the nano zinc oxide and nano titanium dioxide, and the photocatalytic effect of the nano zinc oxide and nano titanium dioxide is increased, thereby improving the antibacterial properties of the nano zinc oxide and nano titanium dioxide, and increasing the antibacterial durability.

[0135] The glaze layer of the present invention is added with a second binder formed by mixing polyvinyl alcohol and bentonite, wherein the polyvinyl alcohol and bentonite can improve the adhesion and hardness of the glaze, and enhance the smoothness, wear resistance and crack resistance of the glaze surface; the bentonite plays the role of a binder and a suspending agent, so that the glaze maintains sufficient consistency and fluidity, avoids sedimentation, and increases the uniformity of the glaze layer.

[0136] The glaze layer of the present invention is added with a stabilizer formed by mixing zirconium silicate and magnesium oxide. Magnesium oxide can enhance the thermal stability of the glaze, and synergistically act with zirconium silicate to reduce cracking and deformation of the glaze layer caused by temperature changes, thereby improving the crack resistance, deformation resistance and wear resistance of the ceramic product. Zirconium silicate has good chemical stability, which makes it unaffected by the ceramic firing atmosphere, thereby ensuring the stability of the glaze and the quality of the finished ceramic product, and can significantly improve the ceramic body-glaze bonding performance, improve the hardness of the ceramic glaze surface, and increase the overall strength of the ceramic. Zirconium silicate can also improve the whiteness and brightness of the glaze layer after glaze firing, thereby enhancing the aesthetics and durability of the ceramic product.

[0137] The glaze layer of the present invention is added with a dispersant prepared by mixing hydroxymethyl cellulose, sodium silicate, sodium hexametaphosphate and polyacrylamide. The hydroxymethyl cellulose can prevent problems such as cracking and deformation caused by water loss during the molding process, thereby improving the crack resistance and deformation resistance of the glaze surface. The hydroxymethyl cellulose can also significantly improve the fluidity of the glaze slurry, make the glaze layer more uniform and delicate, and increase the uniformity of the glaze layer. The sodium silicate increases the negative charge on the surface of the particles to enhance the repulsive force between the particles, thereby achieving a stable dispersion effect, and synergistically improves the fluidity and stability of the glaze with the hydroxymethyl cellulose. It can improve the adhesion and hardness of the glaze, and work synergistically with sodium silicate to make the glaze surface brighter and more uniform, and improve the gloss and wear resistance of the glaze. Polyacrylamide can reduce cracks and defects during the sintering process of the product, thereby increasing the overall crack resistance and deformation resistance of the ceramic. Polyacrylamide can also reduce the viscosity and surface tension of the glaze, increase the spreading speed of the glaze, ensure that the glaze is evenly coated on the surface of the ceramic product, increase the fluidity of the glaze, make the glaze smoother during the coating process, reduce production time and cost, and control the viscosity and wetting properties of the glaze to ensure the stability of the glaze during heating and cooling.

[0138] The glaze layer of the present invention is added with a wear-resistant additive formed by mixing wollastonite and calcium phosphate. Wollastonite can improve the fusibility and fluidity of the glaze, make the glaze adhere to the ceramic surface more evenly, improve the glossiness of the ceramic product, and improve the hardness and wear resistance of the glaze surface; and calcium phosphate improves the optical properties and aesthetics of the glaze surface by changing the microstructure of the glaze surface, while also increasing the hardness and wear resistance of the glaze surface, and reducing the defects of bubbles, bursts and cracks on the glaze surface, thereby improving the quality of the glaze surface. Therefore, the ceramic glaze layer of the present invention also has good density, crack resistance and deformation resistance.

[0139] It should be noted that the above invention content and specific implementation methods are intended to demonstrate the practical application of the technical solution provided by the present invention and should not be interpreted as limiting the scope of protection of the present invention. Those skilled in the art can make various modifications, equivalent substitutions or improvements within the spirit and principles of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. An antibacterial ceramic, characterized in that: The antibacterial ceramic comprises an embryo body and a glaze layer; The embryo body comprises the following raw materials in parts by weight: 30-40 parts of kaolin, 10-15 parts of diatomaceous earth, 5-10 parts of montmorillonite, 10-15 parts of saponite, 5-10 parts of bamboo charcoal powder, 5-10 parts of the first antibacterial agent, 1-5 parts of flux, 5-8 parts of the first binder, and 1-3 parts of reinforcing agent; The glaze layer comprises the following raw materials in parts by weight: 15-25 parts of kaolin, 10-15 parts of diatomaceous earth, 10-15 parts of dolomite, 3-5 parts of tourmaline, 1-3 parts of sodium oxide, 5-10 parts of a second antibacterial agent, 1-3 parts of a second binder, 1-3 parts of a stabilizer, 1-3 parts of a dispersant, and 0.5-1 parts of a wear-resistant additive.

2. The antibacterial ceramic according to claim 1, characterized in that: The antibacterial ceramic comprises an embryo body and a glaze layer; The embryo body comprises the following raw materials in parts by weight: 35 parts of kaolin, 12 parts of diatomaceous earth, 8 parts of montmorillonite, 12 parts of saponite, 7 parts of bamboo charcoal powder, 8 parts of the first antibacterial agent, 3 parts of flux, 6 parts of the first binder, and 2 parts of reinforcing agent; The glaze layer includes the following raw materials in parts by weight: 20 parts of kaolin, 12 parts of diatomaceous earth, 11 parts of dolomite, 4 parts of tourmaline, 2 parts of sodium oxide, 8 parts of the second antibacterial agent, 2 parts of the second binder, 2 parts of the stabilizer, 2 parts of the dispersant, and 0.8 parts of the wear-resistant additive.

3. An antibacterial ceramic according to claim 1 or 2, characterized in that: In the embryo, The first antibacterial agent comprises nano copper oxide, nano silver and at least one selected from zeolite, apatite and zirconium phosphate; The flux comprises potassium oxide powder and sodium silicate; The first binder includes bentonite, sodium carboxymethyl cellulose and sodium silicate; The reinforcing agent comprises inorganic fiber and inorganic powder, wherein the inorganic fiber is selected from at least one of mullite fiber, aluminum silicate fiber and basalt fiber, and the inorganic powder is selected from at least one of aluminum oxide powder, silicon carbide powder and zirconium oxide powder; The particle diameter of the first antibacterial agent is 50-80 nm; the average particle diameters of the flux, the first binder and the reinforcing agent are all 10-15 μm.

4. An antibacterial ceramic according to claim 1 or 2, characterized in that: In the embryo, the particle sizes of the kaolin, diatomaceous earth, montmorillonite, saponite and bamboo charcoal powder are all 300-350 meshes.

5. An antibacterial ceramic according to claim 1 or 2, characterized in that: In the glaze layer, The second antibacterial agent comprises nano zinc oxide, nano titanium dioxide and at least one selected from zinc silicate, zinc phosphate and zinc nitrate; The second binder includes polyvinyl alcohol and bentonite; The stabilizer includes zirconium silicate and magnesium oxide; The dispersant includes hydroxymethyl cellulose, sodium silicate, sodium hexametaphosphate and polyacrylamide; The wear-resistant additives include wollastonite and calcium phosphate; The particle diameter of the second antibacterial agent is 50-80 nm; the average particle diameters of the second binder, stabilizer, dispersant and wear-resistant additive are all 10-15 μm.

6. The antibacterial ceramic according to claim 1, characterized in that: In the glaze layer, the particle sizes of the kaolin, diatomite, dolomite and tourmaline are all 300-350 meshes.

7. A method for preparing the antibacterial ceramic according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: Step 1): weigh the raw materials of the green body according to claim 1 or 2, first weigh kaolin, diatomaceous earth, montmorillonite, saponite, and bamboo charcoal powder and mix them, add water and mix them in a ball mill, remove impurities, and obtain mud; Step 2): Add the first antibacterial agent, flux, first binder and reinforcing agent to the slurry obtained in step 1) and mix thoroughly, filter press and shape into a ceramic body, and then sinter after drying. At room temperature, heat up to 200-300° C. at a uniform rate, and fire for 3-3.5 hours. Then heat up to 850-950° C. at a uniform rate, and fire for 5-6 hours. Then heat up to 1150-1250° C. at a uniform rate, and fire for 2-2.5 hours. Finally, cool naturally to room temperature and fire into a shape. Step 3): weigh the raw materials of the glaze layer according to claim 1 or 2, first weigh and mix kaolin, diatomaceous earth, dolomite and tourmaline, add water and mix in a ball mill, remove impurities, then add sodium oxide, a second antibacterial agent, a second binder, a stabilizer, a dispersant and a wear-resistant additive, and ultrasonically stir at a speed of 400-500r / min for 30-40 minutes to obtain a ceramic glaze slurry; Step 4): The ceramic glaze slurry obtained in step 3) is evenly glazed onto the fired ceramic body obtained in step 2) to form a glaze layer. After the glaze layer on the ceramic body is dried, it is glazed and fired. At room temperature, the temperature is increased to 450°C-550°C in 2-3h, then increased to 950-1050°C in 1-2h, kept warm for 1.5-2min, then increased to 1250-1350°C in 0.5-1h, kept warm for 30min, and finally naturally cooled to room temperature to obtain the antibacterial ceramic.

8. The preparation method according to claim 7, characterized in that: In step 2), the moisture content of the ceramic body is 20-25%; in step 3), the moisture content of the ceramic glaze slurry is 45-55%.

9. The preparation method according to claim 7, characterized in that: In step 4), the thickness of the glaze layer is 0.6-0.8 mm.

Citation Information

Cited By

  • Antibacterial ceramic glaze and preparation method thereof

    CN119874194A

  • Antibacterial ceramic glaze and preparation method thereof

    CN119874194B

  • Antibacterial easy-to-clean ceramic and preparation method thereof

    CN120398560A

  • An antibacterial easy-to-clean ceramic and a method for producing the same

    CN120398560B

  • Ceramic tile with granite texture and preparation method thereof

    CN120647333A